PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KOMITMEN ORGANISASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT BANGUN NUSANTARA BERSAMA SAHABAT - Tamonob, Selfi Yehofa; Agustina, Tri Siwi; Ekowati, Dian (Jurnal Pijar, 2024)
The purpose of this study is to evaluate the impact of transformational leadership, organizational commitment, and organizational culture on employee performance at PT. Bangun Nusantara Bersama Sahabat (BNBS), either separately or together. Data samples were collected from 50 respondents using primary data collection methods. The data was then analyzed using multiple regression method using SPSS software version 25. Findings from the study show that transformational leadership has a significant influence separately and together on employee performance at PT. BNBS. In addition, organizational commitment and organizational culture also have a significant influence separately and together on employee performance. Based on the results of this study, it is recommended that organizational policies focus more on improving programs related to transformational leadership, organizational commitment, and organizational culture because these three factors are proven to improve employee performance in the organization.